United Arab Emirates : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Arab Emirates. (IMF Staff Country Reports; Country Report ;, 2005)
The 2005 Article IV Consultation for the United Arab Emirates reports that the prices in real estate and stock markets, have soared aided by stronger economic fundamentals and investor optimism. An outward-oriented development strategy and prudent financial policies have resulted in impressive economic growth over the years. Economic diversification has advanced rapidly, underpinned by an increasing role of the private sector. There is a need for full rationalization and consolidation of the regulatory oversight related to the capital markets and nonfinancial bank intermediaries.